Educational Module for Ultrasonic Bearing Inspection - Reynoso Jardón, elva (2024)
The document presents the development of an educational module for examining bearings by ultrasound. The development of the mechanical device is described, where an electric motor drives the bearing under inspection, which can be exchanged for other bearings that present a certain degree of damage such as lack of lubrication, oxidation, and dust contamination. The bearing failure types are identified from the ultrasonic decibel (dB) readings generated when operating. Also, the development of an ultrasonic detector that measures the dB of ultrasound that the bearings emit is described, which allows the type of failure to be identified. Likewise, experiments that validate the functionality of the module are shown. The educational module developed is economical and can be replicated in educational institutions, or by the training departments of companies that use bearings in their machinery. In addition, the ultrasonic detector is useful in the industry to find other types of faults that generate ultrasound in machinery and facilities.